1980
DOI: 10.1139/o80-007
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of xanthine oxidase for nitrogen heteroaromatic cation substrates

Abstract: A variety of pyridinium, quinolinium, and benzoquinolinium cations have been investigated as potential substrates for milk xanthine oxidase at pH 9.9 and (or) pH 10.6. Steady-state kinetic parameters (kc, Km and (or) kc/Km) have been evaluated for all substrates which are enzymically oxidized. Simple N-alkyl pyridinium cations are neither substrates nor inhibitors, although N-aryl pyridinium cations are slowly oxidized to the 4-pyridinones. N-Methylpyridinium cations bearing 3-CONH2, 3-CONHCH3, 3-COCH3, 3-CO2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…The ability of XO to reductively activate multiple substrates is documented (Bunting et al, 1980), including the covalent binding of nitroarenes via HX/XO (Fu et al, 1994, Ritter et al, 2002. In the present study, the reaction of NBQ-38 with the highest concentration of HX resulted in the highest level of adduct formation.…”
Section: Discussionsupporting
confidence: 46%
“…The ability of XO to reductively activate multiple substrates is documented (Bunting et al, 1980), including the covalent binding of nitroarenes via HX/XO (Fu et al, 1994, Ritter et al, 2002. In the present study, the reaction of NBQ-38 with the highest concentration of HX resulted in the highest level of adduct formation.…”
Section: Discussionsupporting
confidence: 46%
“…A comparison of our results (Table 3) with previously published data for salts of N-phenylquinoline [9] led to the unambiguous conclusion that introduction of a new benzo-annelated ring increases substantially the biological activity against practically all studied test strains.…”
Section: Experimental Biological Partsupporting
confidence: 74%
“…This trend persists even in condensed derivatives such as benzoquinolinium and benzoquinaldinium salts [7,8]. The biological activity of N-aliphatic benzoquinaldinium compounds is well studied [9,10] due to the difficulty of synthesizing the analogous aryl derivatives. Nevertheless, it was found that replacing an aliphatic substituent on the N atom by an aromatic group increases the antimicrobial activity [11].…”
mentioning
confidence: 99%
“…In many cases N-phenyl compounds surpass their aliphatic analogs. In spite of the large number of studies and the broad aspects of biological and medicinal application (antiseptics, biocides, antimalarials, antitumor, antirecidive, and antipyretic preparations) [6][7][8][9][10][11][12][13][14], the search still goes on for new biologically active compounds in the area of quinoline derivatives [15][16][17][18][19][20][21][22][23][24][25][26].…”
mentioning
confidence: 99%